PENGEMBANGAN MODEL MATERI AJAR MATA KULIAH BAHASA INGGRIS II BERBASIS KEBUTUHAN MAHASISWA PROGRAM STUDI AKUNTANSI SYARIAH STAIN BATUSANGKAR - HENDRA EKA PUTRA (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2016)
This research is derived from the problem in which there was no available reading material of “Bahasa Inggris II” for accounting students, especially Economic Department of Syariah Faculty of State College for Islamic Studies (STAIN) Batusangkar. Relizing that problem, the researchers designed a model of reading material to teach those students as a solution in order to solve their problem in grasping a specific idea that could be found at any English reading materials, especially relating with accounting terms. In validating the model, they asked some comments from experts. Based on the result of the validation, it could be concluded that the model had fulfilled the criteria as a valid one: content validity and construct validity.